PENINGKATAN KEMAMPUAN MENGKLASIFIKASI BANGUN DUA DIMENSI MELALUI PERMAINAN TANGRAM - Withasari, Yurinda (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2018)
The study aims to determine whether the two-dimensional classification capabilities can be enhanced through tangram game. The study was conducted for 14 children aged 4 to 5 years in grade A PAUD Nusantara Palembang, in February-March 2016. The method used is a model of action research Kemmis Mc Taggart. The study was conducted in 16 sessions divided into two cycles. In every cycle there are four stages of activity: planning, action, observation and reflection. Data were analyzed using analysis of quantitative and qualitative analysis. The results showed that children's ability to classify two-dimensional figures can be enhanced through tangram game. Children's ability to classify two-dimensional figures are on a score of 50 on the pre-intervention phase. The ability to classify two-dimensional figures increased to 77.3 at the end of cycle I, and continued to increase to 104 by the end of cycle II. The results of the study implies that the tangram game could be one way to improve the ability to classify two-dimensional figures.Keywords: classification, tangram, and an action research